1987
DOI: 10.1111/j.1476-5381.1987.tb11390.x
|View full text |Cite
|
Sign up to set email alerts
|

New synthetic antagonists of bradykinin

Abstract: 1 A new synthetic bradykinin analogue was found to be an antagonist of bradykinin-induced vascular permeability in rabbit skin. It was effective in equimolar concentrations. 2 These analogues also antagonized the action of bradykinin in contracting the guinea-pig isolated ileum. The mean pA2 values of five different antagonists ranged from 5.3-6.4 respectively, on this preparation. 3 Our observations, together with those of others suggest that these antagonists act on the same receptor types, viz., B2, in rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…Previous studies have indicated that Bk2R mediates bradykinin-induced vascular permeability (24,25). In this report, the C1INH-deficient mice were protected from enhanced vascular permeability by an inhibitor of plasma kallikrein, by a Bk2R antagonist, and by Bk2R-deficiency.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have indicated that Bk2R mediates bradykinin-induced vascular permeability (24,25). In this report, the C1INH-deficient mice were protected from enhanced vascular permeability by an inhibitor of plasma kallikrein, by a Bk2R antagonist, and by Bk2R-deficiency.…”
Section: Discussionmentioning
confidence: 49%
“…2), both B 1 and B 2 receptor signaling may actually enhance angiogenesis. The previous report, which concluded that B 2 receptors were not involved in the enhancement of angiogenesis, was made on the basis of the first-generation B 2 receptor antagonist, a peptide analog of BK, that was not resistant to BKdegrading enzymes, and had a partial agonistic action on B 2 receptors (Hu and Fan, 1993;Schachter et al, 1987). As shown in this experiment, not only the more stable B 2 receptor antagonist, Hoe140, but also the nonpeptide orally active B 2 receptor antagonist, FR173657, significantly reduced angiogenesis (Fig.…”
Section: Angiogenesis and Kininsmentioning
confidence: 99%
“…The former preparation has often been used in earlier investigations of this type of drugs (Vavrek & Stewart, 1985;Regoli et al, 1986;Schachter et al, 1987;Steranka et al, 1988), and the latter has been employed because of its high sensitivity to BK. In addition, the rat duodenum was used because it responds to BK with a relaxation by a mechanism which is not yet fully understood, but involves activation of BK receptors (Boschcov et al, 1984;Griesbacher et al, 1989;Pereira & Paiva, 1989;Altinkurt & Oztiirk, 1990).…”
Section: Isolated Smooth Musclesmentioning
confidence: 99%
“…Although the specificity and high potency of these antagonists has been unequivocally established (Regoli et al, 1986;Griesbacher & Lembeck, 1987;Schachter et al, 1987;Steranka et al, 1988;Francel et al, 1989;Griesbacher et al, 1989), their susceptibility to fast enzymatic degradation limited their usefulness (Griesbacher et al, 1989). Now, new analogues of BK have been synthesized in which unusual amino acids have been inserted with the intention of making the antagonists more resistent to enzymatic cleavage.…”
Section: Introductionmentioning
confidence: 99%